Synthesis and duplex stability of oligonucleotides containing cytosine-thymine analogues. - Lin, P K (1989)
The synthesis of the deoxynucleoside derived from the base P, 6H,8H-3,4-dihydro-pyrimido[4,5-c] [4,5-c] [1,2]oxazin-7-one, 2, and its introduction by established phosphoramidite and H-phosphonate chemistry into oligonucleotides is described. The melting transition temperatures (Tm) of a range of heptadecamer duplexes containing P/A and P/G base-pairs are compared with corresponding ones having N4-methoxycytosine (M) 1 and mismatched normal bases. P/A and P/G pairs allow closely similar duplex stabilities and have the potential to reduce the multiplicity of probes and primers based on amino acid sequences by removing the T/C degeneracy.